Fetal Transcerebellar Diameter/ Abdominal Circumference Ratio as a Gestational Age Independent Parameter for Fetal Growth - Jha, A; Joshi, B; Pradhan, S (Nepal Journal of Obstetrics and Gynaecology, 2014)
Aims: The purpose of this study was to evaluate accuracy of trans-cerebellar diameter / abdominal circumference (TCD/AC) ratio to assess fetal growth. The ratio of TCD with head circumference (HC) and biparietal diameter (BPD) was also determined. Methods: This was a prospective cross-sectional study involving 442 women with uncomplicated singleton gestation between 15-40 weeks. Protocol included obtaining the BPD, HC, TCD and AC in conventional planes and obtaining ratio of TCD with other biometric parameters. Results: We were able to visualize the cerebellum in about 93% of scans. The TCD/ AC ratio remained nearly constant throughout gestational age and was 0.138. The mean TCD/HC ratio was 0.124 and mean TCD/BPD ratio was 0.476. Conclusions: TCD/HC and TCD/BPD ratio showed a small increase towards the completion of gestation while TCD/AC ratio remained nearly constant throughout gestational age. TCD/AC ratio is reliable as a gestational age independent parameter of fetal growth. DOI: http://dx.doi.org/10.3126/njog.v9i2.11770